Keramikken fra pottemagerovnen i Fredsø - Birkals, Asmund; Vegger, Per Bugge (Hikuin, 2001)
The pottery from the kiln in Fredsø By Asmund Birkals and Per Bugge Vegger During the excavation of a small kiln construction in Fredsø, 217 pieces of pottery appeared. Since the construction was quite disturbed by fieldwork at the time of the excavation, there was possibly a good deal more potsherds present when the kiln was abandoned. The most interesting part of the quantity of potsherds was the 32 rims that could be identified. By means of an EVE measurement these potsherds are separated according to the size of their dia- 353 meter, which is between 12 and 22 cm. On the basis of these rims it may be determined that the 32 potsherds represent a minimum of 12 vessels. Of the 12 vessels 11 were thrown with the same basic form, i.e., pots with a flat base. Although the main form has been identified, the vessels of the main group reflect great variation in form. The modest quality of the potsherd material suggests that the potter from Fredsø was not a particularly talented craftsman.